Modeling of renewable energy production from the treatment of slaughterhouse wastewater with ruminal liquor in microbial fuel cells - Valdiviezo Gonzales, Lorgio (2022)
The present study aims to optimize the application of a microbial fuel cell (MFC) in the treatment of slaughterhouse wastewater and the production of electricity. The methodology included the response surface analysis (RSA) to evaluate the effect of three factors: the standard reduction potential, SRP (copper, zinc, and graphite; electrode surface area (ESA), and the doses of ruminal liquor (DOSE). The power density (PD) and the removal of the chemical oxygen demand (COD) were determined as the main response variables. The results indicated that the generation of electrical energy depended significantly on the SRP applied, highlighting the copper-graphite arrangement that generated a maximum PD (0.5685 W/m3) and the graphite-graphite that produced the highest removal of COD (81.33%). Consequently, the RSA produced significant predictive models for the generation of PD (R2 = 0.9485, p = 0.029) and removal of COD (R2 = 0.9888, p = 0.002). MFC is presented as a technology intended to be part of the diversification of renewable energy sources and at the same time recover water resources sustainably.